Ultrasound [videorecording (DVD)] - Kartheiser, Vincent, 1979-; Lopez, Chelsea; Wool, Breeda; Adebimpe, Tunde; Rainsford; Stephenson, Bob, 1967-; Baron, Dana Lyn (Magnolia Home Entertainment, 2022)
After his car breaks down, Glen spends one hell of an odd night with a married couple, setting into motion a chain of events that alter their lives plus those of several random strangers.